Prophylactic protein free synthetic surfactant for preventing morbidity and mortality in preterm infants - (:unkn) unknown (WILEY, 2010)
Background Respiratory distress syndrome (RDS) is caused by a deficiency or dysfunction of pulmonary surfactant. A variety of surfactant products including protein free synthetic surfactant have been developed and tested in the prevention and treatment of RDS. Objectives To assess the effect of prophylactic administration of protein free synthetic surfactant (SS) on mortality, chronic lung disease and other morbidities associated with prematurity in preterm newborns at risk for developing RDS. Subgroup analysis were planned according to the degree of prematurity, surfactant product and dosage schedule. Search strategy Searches were made of the The Cochrane Library, MEDLINE, OVID, EMBASE, CINAHL from 1966 to 2009. In addition, previous reviews including cross references and abstracts from the Society for Pediatric Research were searched. No language restrictions were applied. Selection criteria Randomized and quasi-randomized controlled trials that compared the effect of protein free SS administered to high risk preterm newborns at or shortly after birth in order to prevent RDS, mortality and complications of prematurity. Data collection and analysis Data regarding clinical outcomes was excerpted from the clinical trials by the reviewers. Data were analyzed according to the standards of the Cochrane Neonatal Review Group. Main results Studies of prophylactic administration of protein free SS note a variable improvement in the respiratory status and a decrease in respiratory distress syndrome in infants who receive prophylactic protein free SS. The meta-analysis supports a decrease in the risk of pneumothorax (typical relative risk 0.67, 95% CI 0.50, 0.90), pulmonary interstitial emphysema (typical relative risk 0.68, 95% CI 0.50, 0.93), and neonatal mortality (typical relative risk 0.70, 95% CI 0.58, 0.85). No differences were seen in the risk of intraventricular hemorrhage, necrotizing enterocolitis, bronchopulmonary dysplasia, retinopathy of prematurity and cerebral palsy. The meta-analysis supports an increase in the risk of patent ductus arteriosus associated with prophylactic SS administration (typical relative risk 1.11, 95% CI 1.00, 1.22), and an increase in the risk of pulmonary hemorrhage (typical relative risk 3.28, 95% CI 1.50, 7.16). Authors' conclusions Prophylactic intratracheal administration of protein free synthetic surfactant to infants at risk of developing respiratory distress syndrome has been demonstrated to improve clinical outcome. Infants who receive prophylactic protein free SS have a decreased risk of pneumothorax, a decreased risk of pulmonary interstitial emphysema, and a decreased risk of neonatal mortality. Infants who receive prophylactic protein free SS have an increased risk of developing patent ductus arteriosus and pulmonary hemorrhage.
Keywords: Infant, Newborn; Infant, Premature; Infant, Premature, Diseases [prevention & control]; Pulmonary Surfactants [therapeutic use]; Respiratory Distress Syndrome, Newborn [prevention & control]; Humans; ARTIFICIAL SURFACTANT; PREMATURE-INFANTS; EXOGENOUS SURFACTANT; CONTROLLED-TRIALS; WEIGHING 500; FOLLOW-UP; BIRTH; BABIES; AGE; THERAPY